In-field nucleic acid testing for porcine epidemic diarrhea virus with lateral flow immunoassay - Chen, Wencong; Chen, Jiahao; Ye, Danni; Ai, Xueyan; Luo, Jiayi; Fang, Chenxi; Xiang, Meihua; Wang, Maopeng (Frontiers in Veterinary Science, 2025)
Porcine epidemic diarrhea is a significant disease that damages the global pig industry. The delay between infection and vaccination allows for a 30–70% mortality rate among piglets. Early virus detection is a more effective disease management strategy for pigs. Unfortunately, most methods rely heavily on skilled personnel and sophisticated equipment, which is not ideal in scenarios requiring cost reduction and efficiency. To address these challenges, our study based on one-step RT-PCR and lateral flow strips developed a reliable, field-deployable, and low-cost nucleic acid detection method for PEDV. The whole process takes about 45 min and the testing cost of each sample is low to $0.3. Moreover, this method is simple to operate, it is possible to complete the entire operation without training. Our clinical application demonstrates a robust diagnostic tool for detecting PEDV in field conditions, thereby providing more time for PEDV epidemic emergency response.